Collaborative Work as an Alternative for Writing Research Articles - Nancy Emilce Carvajal Medina; Eliana Edith Roberto Flórez (Universidad Nacional de Colombia, 2014)
Academic writing in English in our context is a significant aspect that can be innovative when a convergence model of writing stages is used along with collaborative work. This article reports on a study aimed at analyzing how collaborative work relates to undergraduate electronics students' academic writing development in English as a foreign language at a Colombian university, following some specific writing stages. Field notes, students' artifacts, and semi-structured interviews were the instruments used to gather information. The results showed that writing is achievable if students can follow stages and receive feedback from the teacher. Additionally, collaborative work allowed students to write research articles in an easy and dynamic way.